Multifunctional Fe2O3/CeO2 nanocomposites for free radical scavenging ultraviolet protection. Issue 70 (12th July 2016) - Cardillo, Dean; Weiss, Martin; Tehei, Moeava; Devers, Thierry; Rosenfeld, Anatoly; Konstantinov, Konstantin
Abstract : In this study we synthesized Fe2 O3 /CeO2 composite nanoparticles with high ultraviolet absorption and free radical scavenging properties for application as multifunctional ultraviolet (UV) filters. Abstract : In this study we synthesized Fe2 O3 /CeO2 composite nanoparticles for application as multifunctional ultraviolet (UV) filters. The precipitation of small ceria (CeO2 ) nanoparticles onto the surface of larger hematite (α-Fe2 O3 ) nanoparticles, results in stronger and more selective absorbance in the (UV) region. Through UV photocatalyst experiments, we show that the addition of these nanocomposite particles significantly reduces the degradation of crystal violet by P25 by scavenging the photogenerated OH˙ radicals.